Unravelling the 2D self-assembly of Fmoc-dipeptides at fluid interfaces. Issue 46 (11th October 2018) - Argudo, Pablo G.; Contreras-Montoya, Rafael; Álvarez de Cienfuegos, Luis; Cuerva, Juan M.; Cano, Manuel; Alba-Molina, David; Martín-Romero, María T.; Camacho, Luis; Giner-Casares, Juan J.
Abstract : Fmoc-dipeptides are self-assembled at the air/liquid interface as a function of their aminoacid sequence. Abstract : Dipeptides self-assemble into supramolecular structures showing plenty of applications in the nanotechnology and biomedical fields. A set of Fmoc-dipeptides with different aminoacid sequences has been synthesized and their self-assembly at fluid interfaces has been assessed. The relevant molecular parameters for achieving an efficient 2D self-assembly process have been established. The self-assembled nanostructures of Fmoc-dipeptides displayed significant chirality and retained the chemical functionality of the aminoacids. The impact of the sequence on the final supramolecular structure has been evaluated in detail using in situ characterization techniques at air/water interfaces. This study provides a general route for the 2D self-assembly of Fmoc-dipeptides.